Christchurch’s houses in 1900 - Watson, Katherine (Architectural History Aotearoa, 2019)
What did Christchurch’s domestic architecture look like in 1900? And how had it evolved to look like that? The demolition of numerous nineteenth-century houses in the city following the earthquakes of 2010 and 2011 provides a unique opportunity to examine the development of the city’s domestic architecture using the techniques of buildings archaeology. This research, which is part of my doctoral thesis, reveals a nuanced picture of how Christchurch’s houses evolved and provides a starting point for understanding why these changes took place, what they might have meant and how they might have related to the city’s identity.